Fluid storage and migration properties of sheared Neptunian dykes. (April 2019) - Parrino, Nicolò; Agosta, Fabrizio; Di Stefano, Pietro; Napoli, Giuseppe; Pepe, Fabrizio; Renda, Pietro
Abstract: Neptunian dykes are widely reported along the Tethyan carbonate platforms and are commonly considered as subsurface baffles or barriers to fluid flow. However, the fluid storage and migration properties of sheared Neptunian dykes are poorly known. For this reason, we investigate the inner structure and fluid flow properties of two Neptunian dykes, which can be characterized by different architectures if involved or not in brittle shearing processes. The dykes strike ca. WNW-ESE and crosscutting the tight Jurassic limestones exposed at Maranfusa Mt., NW Sicily, Italy. The unsheared and sheared Neptunian dykes are almost sub-vertical and at high-angle with respect to the horizontal plane, respectively. The first one includes a homogeneous pelagic limestone infill whereas the second one includes a heterogeneous, marl-rich pelagic limestone infill and also thin veneers of tectonic breccias vertically persistent throughout the investigated outcrop. The sheared Neptunian dyke shows evidences of transtensional faulting, which likely occurred during the early Jurassic up to middle Cretaceous times, with throw up to 2 m. The amount of fracture porosity and equivalent permeability are computed by integrating geological and structural field data with petrographic data obtained from selected samples and Discrete Fracture Network modelling of geocellular volumes representative of the study outcrops. Results are consistent with the sheared Neptunian dyke forming a combined barrier-conduit permeability structure, in which the low-permeability and low–porosity cataclastic core is flanked by a fractured damage zone that enhance the dyke-parallel fluid flow in the subsurface. Accordingly, the amount of fluid storage in the fractured damage zone is sensitively higher than in the surrounding limestone host rock. Data we present highlight that the m-offset, sheared Neptunian dyke, due to its inherited sedimentary infill, is characterized by a permeability structure that it is often associated to large fault zones made up of cataclastic fault cores that impede the cross-fault fluid flow. Highlights: Dyke forms isolated fluid baffle/barrier inhibiting the cross-dyke fluid flow. Dyke in brittle deformation acquire structural architecture typical of faults. Sheared dyke acquires permeability structure typical of larger faults.